e-Research Crosses the Pond: Contrasting transformations in the U.S. and U.K. - Borgman, C; Meyer, E; Lynch, C; Fry, J; Meyer, E; Palmer, C (2008)
e-Research activity is expanding rapidly in the United States and the United Kingdom. e-Research goes by many names, including cyberinfrastructure in the U.S. and e-Science, e-Social Science, and e-Humanities in the U.K., Europe, and elsewhere. Generally, these terms refer to distributed, collaborative, data- and information-intensive research activities. Research practices core to the IS community, such as dissemination, organization and retrieval of knowledge, are likely to undergo fundamental changes and demand new approaches. Furthermore, e-Research offers new funding opportunities to develop IS as a field and engage more strategically with those scientific and scholarly communities we wish to support. The panel will open with a short overview of recent research by each participant to frame discussion. Audience discussion will be organized by a set of key issues of particular interest to information scientists, such the dissemination of knowledge, data sharing, collaborative practices, and research policy and funding. Key issues for discussion: 1. What are the similarities and distinctions between e-Research in the U.S. and the U.K.? 2. How much, and in what forms, are information science scholars collaborating between the U.S., U.K., E.U., and other countries? 3. What role do (and should) information scientists play in the shift towards large, online, collaborative research infrastructures that host data, connections to remote research instruments, software tools, workflows, publications, and a host of other resources? 4. What roles due institutions such as universities, libraries, disciplinary-based societies, and private enterprise play in e-Research? 5. What roles do institutions and individuals play in sharing and curation of research data?